Attentional biases in dysphoria when happy and sad faces are simultaneously presented. (December 2019) - Blanco, Ivan; Poyato, Natalia; Nieto, Ines; Boemo, Teresa; Pascual, Teodoro; Roca, Pablo; Vazquez, Carmelo
Abstract: Background and objective: Difficulties to engage attention to positive stimuli and to disengage attention from negative stimuli are typically found in depression. Yet, most of the evidence supporting these attentional biases comes from experimental paradigms in which emotional information (e.g., happy or sad faces) is simultaneously presented with neutral information. Few studies have explored attentional biases when emotional stimuli of different valence are presented simultaneously. The aim of the present study was to assess visual scan patterns of non-dysphoric and dysphoric participants when emotional information is presented simultaneously. Method: Using an eye-tracker methodology, the gradient relation between attentional biases and depression scores as well as differences between groups in their attentional performance were assessed in non-dysphoric participants (N = 84) and dysphoric participants (N = 58). Three different pairs of faces were used: happy-neutral, neutral-sad, and happy-sad. Results: First, we found that simultaneous presentation of emotional information (i.e., happy vs. negative faces) reduces the magnitude of attentional biases towards positive information. Second, we also found a significant negative relation between attentional biases towards positive information and depression scores. Finally, compared to non-dysphoric participants, dysphoric individuals marginally spent less time attending positive information in both happy-neutral and happy-sad trials. Limitations: The cross-sectional nature of our study does not allow us to make inferences about causality. Further, only one type of simultaneous emotional faces presentation (i.e., happy-sad) was used. Conclusions: These results support the need for further research on the processing of competing emotional stimuli in depression. Highlights: Simultaneous presentation of emotional stimuli reduces healthy attention biases. Attentional biases are distributed following a gradient of depression. High levels of depression increase attentional biases away from positive stimuli.